2017
DOI: 10.1097/md.0000000000007247
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD8+CD28+/CD8+CD28– T cell ratio can sensitively predict poor outcome for patients with complicated Crohn disease

Abstract: Crohn disease (CD) with complications such as penetrating, stricturing, and perianal disease is called complicated CD. The aim of this study is to test the efficiency with which the CD8+CD28+/CD8+CD28– cell balance can predict a subsequent active stage in patients with newly diagnosed complicated CD.Seventeen patients with complicated CD and 48 CD patients with no complications were enrolled. Blood CD8+ T cells were tested from all of the 65 newly diagnosed CD patients upon enrollment. The potential risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Telomere shortening in immune cells have implications for immunocompetence, inflammation, and antibody responses to vaccines (Cohen et al, 2013). CD8 T cells are effector memory cells, which specifically kill damaged or virus-infected cells and are involved in the maintenance of peripheral tolerance to (auto)antigens (Cohen et al, 2013;Dai et al, 2017). CD28+ is a co-stimulatory molecule on CD4 + or CD8 + cells, which stimulates T cell activation and survival (Teijeira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere shortening in immune cells have implications for immunocompetence, inflammation, and antibody responses to vaccines (Cohen et al, 2013). CD8 T cells are effector memory cells, which specifically kill damaged or virus-infected cells and are involved in the maintenance of peripheral tolerance to (auto)antigens (Cohen et al, 2013;Dai et al, 2017). CD28+ is a co-stimulatory molecule on CD4 + or CD8 + cells, which stimulates T cell activation and survival (Teijeira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…13 Later, they proved the imbalance of CD8 + CD28 + /CD8 + CD28 – occurred in inflammatory autoimmune bowel diseases including UC and CD in clinical samples and animal models. 1315,21 In chronic hepatitis B patients, high proportions of the CD8 + CD28 – cell subset and decreased CD8 + CD28 + /CD8 + CD28 – ratio were observed, whereas a significant decrease in the CD8 + CD28 – cell subset and an increase in the CD8 + CD28 + cell subset and in CD8 + CD28 + /CD8 + CD28 – ratio were seen in the patients who received efficient antiviral therapy. 22 In the present study, we found that the CD8 + CD28 – T-cell subset increased in iSLE patients and in the followed-up patients after effective hormonal therapy, which was not correlated with SLEDAI.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It has been reported that the balance between CD8 + CD28 + and CD8 + CD28 − T cells is important in the pathogenesis of some autoimmune diseases such as inflammatory bowel diseases, including ulcerative colitis (UC) and Crohn disease (CD). 1315 What about the balance of CD8 + T-cell subsets in SLE? What about the role of CD8 + CD28 – Treg cells in SLE?…”
Section: Introductionmentioning
confidence: 99%
“…Клетки с фенотипом CD8 + CD28 + являются наивными, наличие этого белка позволяет CD8 + -лимфоцитам взаимодействовать с антигенпрезентирующими клетками и приобретать свою антигенспецифичную активацию. Все CD8 + CD28 --лимфоциты принято считать регуляторными, и для упрощения даже введен индекс CD8 + CD28 + /CD8 + CD28для оценки степени иммуносупрессии [15,16]. На наш взгляд, это некорректно, так как в этой формуле не учитываются цитотоксические Т-лимфоциты, а все клетки, не являющиеся наивными, т. е. прошедшие антигенспецифическую активацию, приравниваются к регуляторным.…”
Section: результатыunclassified